Medium- and time-related effects on hypothermic storage of rat testicular cells - Rageia Elfageih; Ahmed Reda; Kristín Rós Kjartansdóttir; Valentina Pampanini; Olle Söder; Jan-Bernd Stukenborg (Bioscientifica, 2023)
Testicular samples obtained for fertility preservation often need to be transported between clinics. This study aimed to mimic this short-term hypothermic storage (4-8°C) and explore the impact of these conditions and the transport medium composition on prepubertal rat testicular tissue samples. Testicular tissue samples obtained from 7 days post-partum rats were transferred to six compositionally different basal culture media and a balanced salt solution, which had been kept at 4-8°C prior to transfer. The samples were preserved for either 12 or 24 h in these hypothermic conditions. The potential effects of the short-term storage were evaluated by assessing the morphology, measuring the testosterone levels by radioimmunoassay and analysing 96 genes with TaqMan Low-Density Arrays. Levels of gene expression related to energy, apoptosis, and angiogenesis pathways were altered after hypothermic storage for 12 and especially 24 h. We observed only minor differences in gene expression profiles for germ and testicular somatic cells and no differences in tissue morphology and testosterone production levels. Short-term hypothermic storage of testicular tissue with a maximum duration of 24 h does not affect the overall expression profile of testicular cell-specific genes; however, in a minor way, it affects the expression of specific cellular genes.